Responsibility of Land Deed Officials (PPAT) as Participants in The Issue of Sale and Purchase Deeds Cancelled By The Court in West Jakarta - Akmal, Yurizal; Sugiharto, Sugiharto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study aims to determine and analyze the form of implementation of accountability. the answer from the land deed making official (PPAT) as a participating party legal actions regarding the deed of sale and purchase made in West Jakarta and knowing and analyzing the legal consequences of the cancellation of the deed of sale and purchase of land made before the land deed making official (PPAT) by the West Jakarta Court. The results of the research and discussion in this study are: The form of implementation of the responsibility of the land deed making official (PPAT) as a party involved in the legal act on the deed of sale and purchase made in West Jakarta can be seen from the PPAT who carried out the transfer of land rights by making a Deed of Sale and Purchase which was based on a legally flawed due to the deviation of the principle of carelessness of the PPAT in carrying out his position. So that in this study it can be seen that F., SH, M.Kn. and IR, SH, M.Kn. are categorized as parties involved in the legal act on the deed of sale and purchase where it is categorized as joint participation in falsifying authentic documents and money laundering on the deed which is a legal product made so that the defendants are burdened with principal and additional criminal penalties which result in the deed being declared null and void by law and the legal consequences of the cancellation of the deed of sale and purchase of land made before the land deed making official (PPAT) by the West Jakarta court are that it is declared null and void (niegtigheid van rechtswege) and all are returned to their original state to the late. CIM, which in this case is the heir of the deceased, is back to NZ Zubir, where due to the carelessness of the PPAT in making its legal product based on the decision Number: 248 / P Pid.B / 2022 / PN Jkt.Brt and is burdened with imprisonment for 2 years and 8 months each, a fine of Rp. 1,000,000,000, - (one billion rupiah) but if the fine is not paid then it is replaced with imprisonment for 1 month each.Keywords: Accountability, PPAT, Participation, Making AJB